1998
DOI: 10.1016/s0741-5214(98)70163-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of human femoral arteries after cryopreservation

Abstract: The cryopreservation method used provided a limited preservation of HFAs contractility, a good preservation of the endothelium-independent relaxant responses, but no apparent preservation of the endothelium-dependent relaxation. It is possible that further refinements of the cryopreservation protocol, such as a slower rate of cooling and a more controlled stepwise addition of dimethyl sulfoxide, might allow better post-thaw functional recovery of HFAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Similar observations have been made in the recent studies of human arteries. Cryopreserved human internal mammary arteries and femoral arteries had both poorly preserved smooth muscle functions and endothelial functions [10,11]. Freeze substitution of cryopreserved blood vessels demonstrates high levels of extracellular ice formation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have been made in the recent studies of human arteries. Cryopreserved human internal mammary arteries and femoral arteries had both poorly preserved smooth muscle functions and endothelial functions [10,11]. Freeze substitution of cryopreserved blood vessels demonstrates high levels of extracellular ice formation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In cryopreserved human internal mammary arteries and femoral arteries, both smooth muscle functions and endothelial functions were poorly-preserved. 10,25 Classical cryopreservation, with low concentrations DMSO, does a reasonable job of cell preservation by preventing intracellular ice formation; but it is a very poor method for preserving tissue. Even when all major cryopreservation variables are controlled, there is a limit, largely a function of tissue volume and geometry, beyond which traditional cryopreservation methods do not work consistently.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of the postthaw contractility for KCl to less than 40% of fresh tissue has been observed in human coronary [7], internal mammary, [8] and human femoral arteries [4], whereas the maximal response to norepinephrine was reduced to 75% in human mesenteric arteries [5], to 24% for human internal mammary arteries, [5] or to 7% in human femoral arteries [4]. Freezing of vascular preparations generally results in a loss of contractile responsiveness [4,9,10]. In addition, Ku et al have shown that an identical cryopreservation procedure applied to canine and human coronary arteries resulted in a greater loss of contractility in human arteries, indicating vessel to vessel variability in the susceptibility to cryoinjury [11,12].…”
Section: Discussionmentioning
confidence: 92%
“…The maximal contractile responses were in the range of 13 to 27% of the responses in unfrozen pig aortas with noradrenaline and also with KCl, which provokes a contraction strictly dependent on Ca 2ϩ influx through voltage-operated channels. A reduction of the postthaw contractility for KCl to less than 40% of fresh tissue has been observed in human coronary [7], internal mammary, [8] and human femoral arteries [4], whereas the maximal response to norepinephrine was reduced to 75% in human mesenteric arteries [5], to 24% for human internal mammary arteries, [5] or to 7% in human femoral arteries [4]. Freezing of vascular preparations generally results in a loss of contractile responsiveness [4,9,10].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation